IEEE Antennas and Propagation Society International Symposium (IEEE Cat. No.02CH37313)
DOI: 10.1109/aps.2002.1016311
|View full text |Cite
|
Sign up to set email alerts
|

Particle swarm, genetic algorithm, and their hybrids: optimization of a profiled corrugated horn antenna

Abstract: Introduction Genetic Algorithms (CA) have proven to be a useful method of optimization for difficult and discontinuous multidimensional engineering problem. A new method of optimization, Particle Swarm Optimization (PSO), is able to accomplish the same goal as GA optimization in a new and faster way [l]. The purpose of this paper is to investigate: the foundations and performance of the two algorithms when qplied to the design of a profiled corrugated horn antcnna. Also investigated is the possibility of hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0
6

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(123 citation statements)
references
References 2 publications
(2 reference statements)
0
117
0
6
Order By: Relevance
“…During the last decades various optimization techniques like Genetic Algorithm (GA), Ant Colony Optimization (ACO), Particle Swarm Optimization (PSO), and Bees Algorithm (BA) [1][2][3][4][5][6][7] in addition to many hybrid optimization methods [8][9][10] have been used for optimizing parameters in the antenna and antenna arrays problem. Each of these methods has its own pros and cons.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades various optimization techniques like Genetic Algorithm (GA), Ant Colony Optimization (ACO), Particle Swarm Optimization (PSO), and Bees Algorithm (BA) [1][2][3][4][5][6][7] in addition to many hybrid optimization methods [8][9][10] have been used for optimizing parameters in the antenna and antenna arrays problem. Each of these methods has its own pros and cons.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some researchers did try to combine the power of EAs and PSO. In [19], a hybrid algorithm of GA and PSO is proposed and the results showed that this algorithm outperforms simple PSO and simple GA. However, this PSO-GA hybrid is just a simple combination of the two algorithms, which is done by taking the population of PSO when the improvement starts to level off and using it as the starting population of GA.…”
Section: Challenges and Proposed Solutionmentioning
confidence: 99%
“…PSO, based on the movement and intelligence of swarms, was a robust stochastic evolutionary computation technique inspired in the behavior of bee flocks [15]. It has been shown in certain instances to outperform other methods of optimization like genetic algorithms (GA) in the electromagnetic community [16]. Figure 1.…”
Section: Parasitic Absorption Of Metal Nanoparticles In the Plasmonicmentioning
confidence: 99%